2020
DOI: 10.1093/mnras/staa2372
|View full text |Cite
|
Sign up to set email alerts
|

Thermal desorption of carbon monoxide from model interstellar ice surfaces: revealing surface heterogeneity

Abstract: Temperature programmed desorption has been used to probe the distribution of binding energies of carbon monoxide (CO) to molecular solid thin films of astrophysical relevance. Measurements are reported for solid water (both compact amorphous solid water and crystalline water), ammonia and methanol surfaces. Binding energy distributions and optimised pre-exponential factors based on the inversion method are tabulated. These are compared to existing data on these systems and astrophysical conclusions drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This was deliberately done to ensure that there are pure volatile and supervolatile ice domains in the mixed molecular ices. This method differs slightly from previous methods [Malyk et al 2007;Martin-Domenech et al 2014], where either observed mixing ratios were used for mixed molecular ices or layered ices [Acharyya et al 2007;Bar-Nun et al 2013;Collings et al 2004;Collings et al 2003;Collings et al 2005;Edridge et al 2013;Fayolle et al 2011;Fraser et al 2004;Fuchs et al 2006;Greenberg et al 2017;Muller et al 2018;Rawlings et al 2006;Taj and McCoustra 2020], or pure ices were studied through TPD [Isokoski et al 2014;Mate et al 2008]. In astrophysical environments it is unlikely that pure supervolatile ice grains exist where no other molecule is present in the ice grains, such as pure CO ice, though pure CO ice domains could exist in an ice grain that contains other volatiles as well.…”
Section: Tpd Of Mixed Molecular Icesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was deliberately done to ensure that there are pure volatile and supervolatile ice domains in the mixed molecular ices. This method differs slightly from previous methods [Malyk et al 2007;Martin-Domenech et al 2014], where either observed mixing ratios were used for mixed molecular ices or layered ices [Acharyya et al 2007;Bar-Nun et al 2013;Collings et al 2004;Collings et al 2003;Collings et al 2005;Edridge et al 2013;Fayolle et al 2011;Fraser et al 2004;Fuchs et al 2006;Greenberg et al 2017;Muller et al 2018;Rawlings et al 2006;Taj and McCoustra 2020], or pure ices were studied through TPD [Isokoski et al 2014;Mate et al 2008]. In astrophysical environments it is unlikely that pure supervolatile ice grains exist where no other molecule is present in the ice grains, such as pure CO ice, though pure CO ice domains could exist in an ice grain that contains other volatiles as well.…”
Section: Tpd Of Mixed Molecular Icesmentioning
confidence: 99%
“…ensure that there are pure volatile and supervolatile ice domains in the mixed molecular ices. This method differs slightly from previous methods, 19,20 where either observed mixing ratios were used for mixed molecular ices or layered ices, [21][22][23][24][25][26][27][28][29][30][31][32][33] or pure ices were studied through TPD. 34,35 In astrophysical environments it is unlikely that pure supervolatile ice grains exist where no other molecule is present in the ice grains, such as pure CO ice, though pure CO ice domains could exist in an ice grain that contains other volatiles as well.…”
Section: Tpd Of Mixed Molecular Icesmentioning
confidence: 99%
“…coming to the fore with studies likewise on a variety of carbonaceous [168], siliceous [167,198,199] and ice surfaces [168,198,200]. As an illustrative example, we consider the study of CO desorption from amorphous silica by Taj and co-workers [198,199].…”
Section: Thermal Processesmentioning
confidence: 99%
“…However, setting up the physicochemical conditions of the IS medium realistically is technically very difficult, and reproducing the actual composition of grain analogues (e.g., dirty ice mantles) is also tricky [61]. Additionally, information derived from the experiments (e.g., activation and diffusion energies) is dependent on the physico-chemical model adopted to interpret the results, as in the temperature programmed desorption (TPD) experiments [62].…”
Section: Introductionmentioning
confidence: 99%